(untitled) (American Journal of Pedagogical and Educational Research, 2023)
It is known that in our country, classical professions, including crafts, have long evolved, creating various fancy items, making equipment that we use in our daily lives, thereby bringing a sense of self-esteem to people with their work, have reached a high level of value. Today, the lines of goods and goods (works, services) produced by craftsmen in Uzbekistan have reached 34 out of 25. They are currently producing products for the domestic and foreign markets. These products are also very significant in their quality, artistically Highness, naturalness and harmonization of our national identity, national traditions, historical traditions in themselves.